AS A MOTIVATIONAL FACTOR IN THE MASTERING OF SUBJECTS BY FUTURE TEACHERS IN EDUCATIONAL ACTIVITIES (International journal of artificial intelligence, 2026)
Тhe article analyzes the process of future educators mastering educational subjects in educational activities as a factor in increasing the motivational characteristics of interest in the profession. The craving for knowledge also determines the activity, ability and level of work on oneself in the main driving process of professional formation.